A holistic approach to understanding match demands in women's soccer - Harkness-Armstrong, A. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
Fédération Internationale de Football Association (FIFA) has described womens football as the leading opportunity for growth in football (FIFA, 2021). Indeed, womens football has witnessed substantial growth in participation, investment, and research in recent years as key stakeholders attempt to develop the sport at both grassroots and elite levels (Harkness-Armstrong et al., 2022). An important area of research activity has been understanding the match demands which players experience as this appears important for informing training practice design. Most research to date has focused on senior match-play with only ~10% of studies considering youth players. Data shows that senior players cover 9-11 km per match, with approximately one quarter of total distance covered at high-speed (Scott et al., 2020). The physical demands of the womens game continue to evolve, with teams covering ~30% more distance in the highest speed zone (> 23 km.h-1) in the 2019 FIFA Womens World Cup compared to the 2015 edition (FIFA, 2019). Whilst there is a growing literature base citing the physical match demands of womens soccer, there is a lack of evidence considering a more holistic approach which also evaluates the tactical and technical demands and their interaction with the physical dimension. Running with the ball requires an additional energy cost (Piras et al., 2017) and consequently an integrated approach to match analysis should be considered.